Structural insights into the functional roles of 14-3-3 proteins - Obsilova, Veronika; Obsil, Tomas (Frontiers in Molecular Biosciences, 2022)
Signal transduction cascades efficiently transmit chemical and/ or physical signals from the extracellular environment to intracellular compartments, thereby eliciting an appropriate cellular response. Most often, these signaling processes are mediated by specific protein-protein interactions involving hundreds of different receptors, enzymes, transcription factors, and signaling, adaptor and scaffolding proteins. Among them, 14-3-3 proteins are a family of highly conserved scaffolding molecules expressed in all eukaryotes, where they modulate the function of other proteins, primarily in a phosphorylation-dependent manner. Through these binding interactions, 14-3-3 proteins participate in key cellular processes, such as cell-cycle control, apoptosis, signal transduction, energy metabolism, and protein trafficking. To date, several hundreds of 14-3-3 binding partners have been identified, including protein kinases, phosphatases, receptors and transcription factors, which have been implicated in the onset of various diseases. As such, 14-3-3 proteins are promising targets for pharmaceutical interventions. However, despite intensive research into their protein-protein interactions, our understanding of the molecular mechanisms whereby 14-3-3 proteins regulate the functions of their binding partners remains insufficient. This review article provides an overview of the current state of the art of the molecular mechanisms whereby 14-3-3 proteins regulate their binding partners, focusing on recent structural studies of 14-3-3 protein complexes.